2019
DOI: 10.1111/jwas.12651
|View full text |Cite
|
Sign up to set email alerts
|

Choice preference of diets with different protein levels depending on water temperature in Nile tilapia

Abstract: This study tested a choice feeding model for Nile tilapia that allowed the selection of a higher or lower protein content in the diet depending on water temperature. Nile tilapia were reared in twelve 200-L tanks for 63 days with 12 fish (body weight 38 g/fish at start) per tank. Two temperatures (22 or 30 C) and two color combinations (yellow and red each) for a two-component diet containing 30% (low) and a 38% (high) crude protein content based on dry matter were used. High water temperature (30 vs. 22 C) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
0
7
0
1
Order By: Relevance
“…EFFECT OF FEED PROCESSING ON THE PRODUCTIVE PERFORMANCE OF NILE TILAPIA Some authors report that protein levels above 24 or 26% always satisfy the growth requirements for juvenile tilapia. 20,21 Likewise, El-Wahab et al 22 suggested that diets with a protein content of around 34% are acceptable for tilapia farming. This result could be due to the content of amino acids present in the treatments since the amino acids required to improve tilapia performance are lysine, arginine, phenylalanine, isoleucine, leucine, methionine, threonine, and valine or a mixture of methionine, cystine, valine, and lysine.…”
Section: Discussionmentioning
confidence: 99%
“…EFFECT OF FEED PROCESSING ON THE PRODUCTIVE PERFORMANCE OF NILE TILAPIA Some authors report that protein levels above 24 or 26% always satisfy the growth requirements for juvenile tilapia. 20,21 Likewise, El-Wahab et al 22 suggested that diets with a protein content of around 34% are acceptable for tilapia farming. This result could be due to the content of amino acids present in the treatments since the amino acids required to improve tilapia performance are lysine, arginine, phenylalanine, isoleucine, leucine, methionine, threonine, and valine or a mixture of methionine, cystine, valine, and lysine.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen was measured in a high temperature elemental analyzer (Vario Max®, Elementar, Hanau, Germany). The calcium content was determined by atomic absorption spectrometry, phosphorus colorimetrically [ 33 , 34 ]. For the analysis of crude fiber the fat- and ash-free samples were cooked with acid (1.25% sulphuric acid) and alkaline (1.25% sodium hydroxide) solutions in a crude fibre determination device (Fibertec™ 2010 Hot Extractor, Fa.…”
Section: Case Historymentioning
confidence: 99%
“…Nitrogen was measured in a high temperature elemental analyzer (Vario Max ® , Elementar, Hanau, Germany). The calcium content was determined by atomic absorption spectrometry, phosphorus colorimetrically [33,34]. For the analysis of crude ber the fat-and ash-free samples were cooked with acid (1.25% sulphuric acid) and alkaline (1.25% sodium hydroxide 1.25) solutions in a crude bre determination device (Fibertec™ 2010 Hot Extractor, Fa.…”
Section: Case Historymentioning
confidence: 99%